Defining empowerment for older people living with dementia from multiple perspectives: A qualitative study. (February 2021) - van Corven, Charlotte T.M.; Bielderman, Annemiek; Wijnen, Mandy; Leontjevas, Ruslan; Lucassen, Peter L.B.J.; Graff, Maud J.L.; Gerritsen, Debby L.
Abstract: Background and objectives: The concept of empowerment seems promising for people living with dementia to live their life as they want to for as long as possible. Therefore, this study aimed to explore what the concept of empowerment means and includes for people living with dementia from the perspectives of people living with dementia themselves, their informal caregivers, and healthcare professionals. Research design and methods: Qualitative research using focus group discussions and individual interviews with people living with dementia ( n  = 15), informal caregivers ( n  = 16) and healthcare professionals ( n  = 46) to explore perspectives on empowerment. Audio-recordings were transcribed verbatim, and separately analyzed by two researchers using inductive thematic analysis. Results: Four themes were identified as important aspects of empowerment: (1) having a sense of personal identity, (2) having a sense of choice and control, (3) having a sense of usefulness and being needed, and (4) retaining a sense of worth. Based on these themes, a conceptual framework of empowerment for older people living with dementia was developed. Empowerment takes place within the person living with dementia, but is achieved through interaction with their environment. The four themes seem to be important both at home and in nursing homes, and in different stages of dementia. However, practical detailing of support differed. Discussion and implications: Our empowerment framework may provide a basis for developing interventions to empower people living with dementia and to strengthen (in)formal caregivers in this empowerment process. Support for people living with dementia must be adjusted to their personal situation and individual capabilities.